(In)consistency matters: An account of understanding the perception of inconsistent expressions on social media - Li, Pengxiang; Cho, Hichang; Qin, Yuren (Frontiers in Psychology, 2022)
In their daily use of social media, most people cannot maintain consistency in every message they present, leading observers to experience a feeling of inconsistency. Building on computer-mediated interpersonal theories (i.e., attribution theory, warranting theory and authenticity model of CMC), this study aims to explore how people interpret and reconcile perceived inconsistent expressions on social media. Through thematic analysis of data obtained from six focus groups, two main themes were extracted: the origin of perceived inconsistency on social media and the strategies for reconciling perceived inconsistency. Specifically, three forms of perceived inconsistent information were identified: those within the same account; those between public and private accounts; and those between online and offline settings. Additionally, three types of reconciliation strategies were distilled from participants’ narratives: relying on authentic representation; engaging in perspective-taking to compensate for situational factors; and inferring inner motives behind acting inconsistently. With these two themes, this study proposes a two-stage model of processing inconsistency (i.e., reasoning from inconsistency to consistency) in computer-mediated communication. This model suggests that several factors—including perceived authenticity, social categorical cues, and relationship or familiarity between observers and a presenter—are involved in perceiving inconsistent information and determine the outcomes of interpersonal evaluations. These findings enhance our understanding of online interpersonal perceptions.